1988
DOI: 10.1111/j.1432-1033.1988.tb14338.x
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning, nucleotide sequence and expression of the gene for arylsulfatase in the sea urchin (Hemicentrotus pulcherrimus) embryo

Abstract: Arylsulfatase is known to be synthesized in large amounts at the early gastrula stage of sea urchin development. We determined the amino acid sequence of a portion of the purified sea urchin embryonic arylsulfatase, and then isolated a cDNA clone for arylsulfatase by screening a sea urchin plutei lambda gt10 cDNA library with an oligodeoxynucleotide probe synthesized according to the determined amino acid sequence. The longest cDNA clones were selected and the nucleotide sequence determined. The cDNA is 2422 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…O/A patterning has been studied most in the ectoderm and, thus, many gene products with asymmetric distribution about the axis have been identified. Aboral genes include Spec1 and Spec2 (Lynn et al, 1983), CyIIIa actin (Cox et al, 1986), arylsulfatase (Sasaki et al, 1988), Hox8/Hbox1 (Angerer et al, 1989), SpMTA (Nemer et al, 1995) and P3A2 (Calzone et al, 1991); whereas oral genes include EctoV (Coffman and McClay, 1990) Otx (Li et al, 1997a;Yuh et al, 2002), SpCOUP-TF (Vlahou et al, 1996), BMP2/4 , PlOtp (Di Bernardo et al, 1999), Brachyury (Gross and McClay, 2001) and goosecoid (Angerer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…O/A patterning has been studied most in the ectoderm and, thus, many gene products with asymmetric distribution about the axis have been identified. Aboral genes include Spec1 and Spec2 (Lynn et al, 1983), CyIIIa actin (Cox et al, 1986), arylsulfatase (Sasaki et al, 1988), Hox8/Hbox1 (Angerer et al, 1989), SpMTA (Nemer et al, 1995) and P3A2 (Calzone et al, 1991); whereas oral genes include EctoV (Coffman and McClay, 1990) Otx (Li et al, 1997a;Yuh et al, 2002), SpCOUP-TF (Vlahou et al, 1996), BMP2/4 , PlOtp (Di Bernardo et al, 1999), Brachyury (Gross and McClay, 2001) and goosecoid (Angerer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In heterokaryon studies of an electrophoretic variant of arylsulfatase, it was shown that the cys-3+ gene product could activate arylsulfatase gene expression in a trans-nuclear manner, whereas scon+ was limited to intranuclear control of arylsulfatase expression (6,26,28). Recent molecular studies with a number of arylsulfatases (e.g., human [45] and sera urchin [40] …”
mentioning
confidence: 99%
“…The Ars gene is actively transcribed during post gastrula stages, and the accumulation of arylsulfatase mRNA may reach about 1% of total mRNAs (Sasaki et al, 1988); the C15 enhancer in the first intron is apparently very strong. Therefore, the Ars enhancer could influence the promoter of the neighboring genes.…”
Section: Boundary Of Chromatinmentioning
confidence: 99%
“…HpArs (Sakamoto et al, 1997;Kiyama et al, 1998), Spec2a (Gan et al, 1995) and Endo16 (Yuh et al, 1998) have been reported as direct target genes of Otx in sea urchin embryo. HpArs is transcriptionally activated late in blastula, and after the gastrula stage it is expressed exclusively in the aboral ectoderm throughout embryonic development (Sasaki et al, 1988;Akasaka et al, 1990aAkasaka et al, , 1990b. In order to detect cis-regulatory elements responsible for the transcriptional activity of genes, we introduce reporter(Luc)-fusion constructs into fertilized eggs.…”
Section: Otx Target Genementioning
confidence: 99%
See 1 more Smart Citation